2018
DOI: 10.9758/cpn.2018.16.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Treatment of Major Depressive Episodes with Mixed Features: A Systematic Review

Abstract: We reviewed clinical studies investigating the pharmacological treatment of major depressive episodes (MDEs) with mixed features diagnosed according to the dimensional criteria (more than two or three [hypo]manic symptoms+principle depressive symptoms). We systematically reviewed published randomized controlled trials on the pharmacological treatment of MDEs with mixed features associated with mood disorders, including major depressive disorder (MDD) and bipolar disorder (BD). We searched the PubMed, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, a double-blind placebo control study revealed that lurasidone improved depressive symptoms without affecting manic symptoms in mixed-feature variants ( 83 ). Several studies have compared mood-stabilizing atypical antipsychotics (including olanzapine, lurasidone, brexpiprazole, ziprasidone, and cariprazine) with placebo, assessing the efficacy in the acute phase of presumptive mixed-feature variants ( 40 , 84 , 85 ). The available studies support the expected benefits of mixed-feature variants, whereas the overall effect may be similar in these mood-stabilizing atypical antipsychotics ( 40 , 84 , 85 ).…”
Section: Clinical Evaluation Of Lurasidone and Preclinical Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a double-blind placebo control study revealed that lurasidone improved depressive symptoms without affecting manic symptoms in mixed-feature variants ( 83 ). Several studies have compared mood-stabilizing atypical antipsychotics (including olanzapine, lurasidone, brexpiprazole, ziprasidone, and cariprazine) with placebo, assessing the efficacy in the acute phase of presumptive mixed-feature variants ( 40 , 84 , 85 ). The available studies support the expected benefits of mixed-feature variants, whereas the overall effect may be similar in these mood-stabilizing atypical antipsychotics ( 40 , 84 , 85 ).…”
Section: Clinical Evaluation Of Lurasidone and Preclinical Potentialsmentioning
confidence: 99%
“…Several studies have compared mood-stabilizing atypical antipsychotics (including olanzapine, lurasidone, brexpiprazole, ziprasidone, and cariprazine) with placebo, assessing the efficacy in the acute phase of presumptive mixed-feature variants ( 40 , 84 , 85 ). The available studies support the expected benefits of mixed-feature variants, whereas the overall effect may be similar in these mood-stabilizing atypical antipsychotics ( 40 , 84 , 85 ). To explore the efficacy of 5-HT7R antagonism against mixed-feature variants, the detailed clinical effects of conventional mood-stabilizing atypical antipsychotics and antidepressants on mixed-features variants need to be clinically investigated.…”
Section: Clinical Evaluation Of Lurasidone and Preclinical Potentialsmentioning
confidence: 99%
“…Affrontive symptoms of hypo/mania are correlated with both cognitive and somatic symptoms of depression (O’Rourke et al., 2021 ). This allows us to measure mixed depression and hypo/mania symptoms, common to most BD mood episodes (Shim et al., 2018 ). Developing measures specifically for EMA is ideal; most researchers instead cherry‐pick items from existing measures with limited pilot testing (i.e., psychometric properties untested; Trull & Ebner‐Priemer, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several recent papers, not reviewed here summarize the limited data on treatment of "unipolar " depression with mixed features (33,(74)(75)(76)(77) which may or may not proceed to bipolar disorder or in part have its own signature. As can be seen by the recency of papers quoted, up to date knowledge of the evolving literature is important as guidelines are already outdated.…”
Section: Specific Treatments For Depression With Family History Of Bimentioning
confidence: 99%